The Influence of Jigsaw Type Cooperative Learning Model on Students' Understanding of Islamic History Material at MI An Nafiiyah 2 - Muslim (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to analyze the effect of the Jigsaw cooperative learning model on students' understanding of Islamic History material at MI An Nafiiyah 2. The research method used is quantitative with a quasi-experimental design. The research sample consisted of two classes, namely the experimental class using the Jigsaw model and the control class using conventional methods. The research instruments were in the form of comprehension and observation tests. The results of the study showed that the application of the Jigsaw cooperative learning model had a positive effect on students' understanding. Students who learned with the Jigsaw model showed a higher increase in understanding scores compared to students who learned with conventional methods. This is due to the active interaction between students in small groups that allows them to share information and strengthen conceptual understanding. In addition, the Jigsaw model also improves students' social skills and activeness in the learning process. Based on these findings, it can be concluded that the Jigsaw cooperative learning model is effective in improving students' understanding of Islamic History material. Therefore, it is recommended for educators to apply this model as an alternative in teaching Islamic History in order to create more interactive and meaningful learning.